Single cell oils production and application - Nataša FIDLER; Berthold KOLETZKO; Thorsten U. SAUERWALD (Acta Agriculturae Slovenica, 1999)
Microorganisms have been receiving increased attention as sources of novel lipids. Those that accumulate more than 20-25 % of their biomass as oil may be termed oleaginous and their oils single cell oils (SCOs), unicellular oils or microbial oils. For the lipid accumulation in yeasts, moulds and eukaryotic algae, but not in bacteria, the presence of enzyme ATP-cytrate lyase is of vital importance. This enzyme serves to produce acetyl-CoA, which is the substrate for fatty acid biosynthesis. Nitrogen limitation is the most frequently used condition to favour lipid accumulation. Oleaginous organisms differ from nonoleaginous ones in being able to convert carbon from the growth medium into the intracellular lipid, after the nitrogen has been depleted from the medium, provided that the supply of carbon stays plentiful. Biosynthetic pathways of n-6 and n-3 polyunsaturated fatty acids from the saturated and monounsaturated precursors with the chain elongations and desaturations are presented. The suitability of an microalgal triglyceride-SCO highly enriched in docosahexaenoic acid (DHASCOŇ) as a source for nutritional supplementation for formula milk is compared to fish oil. Some safety evaluation studies of SCOs are presented. For the safe use of SCOs in infant formulas even further safety studies should be performed. By growing microalgal strains in a medium containing D-[1-13C]glucose, SCOs enriched with the stable isotope 13C can be produced. Some examples of recent research and diagnostic applications of 13C-labelled SCOs to study fatty acid metabolism are outlined. In conclusion, SCOs in combination with stable isotopes have become indispensable to study metabolic pathways.